Improving Investigative Site Contact Options on Clinical Trial Registries: Making It Easier for Patients to Find Clinical Trials. (September 2017) - Polidori, Christa Patterson; Su, Mandy S.; Jakee, Kelsey; Hodge, Keir; Ancona, Crystal; Yoder, Joseph
Background: Survey data has suggested a gap between individuals willing to participate in a clinical trial and those who enroll. Clearer research must be done to better understand this discrepancy and the accessibility of patient-desired information, such that steps can be identified to assist sponsors in empowering patients to drive their own clinical trial search journey. Methods: Patients, sponsors, and health care professionals were engaged through surveys and advisory boards to determine the ideal information for sponsors to provide during a clinical trial search. Public registries were analyzed to assess availability of basic investigator and site contact location information. Results: Data reiterated the need for patients to have easy and unambiguous methods of connecting with the clinical trial site. Analysis of data on registries prove that sponsors have the opportunity to better utilize contact information on databases to enable a patient's clinical trial search journey. Conclusions: More robust disclosure of site location and contact details on public registries could lay the foundation for a more user-friendly clinical trial search. Allowing sites autonomy in site contact methods while promoting accessibility will facilitate the connection of interested patients with appropriate trial opportunities.